Planning of models of the distributed processing of data with a virtual server - Боровик, В. М. (Problems of Informatization and Control, 2009)
The model of servers of databases as queuing system is explored with priorities. The method of optimization of priorities and principles of practical application of research results is determined in the systems “client-server” with the distributed processing of data